Dyadic Death via Cut-throating: A Case Report - Garan, Abdurrahman; Alıncak, Soner; Asar, Selman; Büken, Bora (The Bulletin of Legal Medicine, 2024)
Cut-throating is most commonly homicidal, but can also occur as a result of suicide or accident. We present two cases of cut-throating consist of one homicide and one suicide handled by the husband in the same scene. Causes of death for both are reported as “as a result of bleeding due to major vascular damages caused by sharp force injury”. According to judicial investigation; the couple had been in process of divorcing and that night the man firstly killed his wife and then himself by cut-throating with a knife while their kids present. We present this case because it involves both homicide and suicide handled by the same hands with the same method in an event. We aimed to emphasize the importance of the differences in the findings obtained from the crime scene and the corpse in determining the origin in deaths by cut-throating.